2022
DOI: 10.1590/1809-6891v22e-71567e
|View full text |Cite
|
Sign up to set email alerts
|

Practical diet with total replacement of fishmeal by soybean meal for Nile tilapia: growth performance and health effects

Abstract: This study aimed to evaluate the growth performance and animal health in juveniles of Nile tilapia (Oreochromis niloticus) fed a practical diet with total replacement of fishmeal (FM) by soybean meal, as well the effect on survival, following pathogenic challenge with Aeromonas hydrophila. Two hundred juveniles of Nile tilapia were stored in 8 tanks (800 L). The experiment consisted of two treatments: a commercial diet formulated with FM (control) and a practical diet with total replacement of FM by soybean me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Other studies have revealed similar data, with a low growth rate and high feed conversion in rainbow trout (Oncorhynchus mykiss)(Belghit et al 2014) and yellowtail (Seriola dorsalis) (Garcia-Organista et al 2019), requiring the addition of this amino acid in crystalline form(Browdy et al 2012, Michelato et al 2018, Nunes et al 2014. Therefore, growth performance is also correlated with methionine level in the diet, which, despite being below the recommended level for the species, good results can be justified by the sum of "methionine + cysteine", because the data obtained in this research are similar to those of fish produced with a commercial diet(Stockhausen et al 2022)…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Other studies have revealed similar data, with a low growth rate and high feed conversion in rainbow trout (Oncorhynchus mykiss)(Belghit et al 2014) and yellowtail (Seriola dorsalis) (Garcia-Organista et al 2019), requiring the addition of this amino acid in crystalline form(Browdy et al 2012, Michelato et al 2018, Nunes et al 2014. Therefore, growth performance is also correlated with methionine level in the diet, which, despite being below the recommended level for the species, good results can be justified by the sum of "methionine + cysteine", because the data obtained in this research are similar to those of fish produced with a commercial diet(Stockhausen et al 2022)…”
supporting
confidence: 52%
“…The mixture was then homogenized in a horizontal paddle mixer for 4 minutes and ground again to a size of 800 µm. It was then extruded at 105 °C using an extruder (FERRAZ®, Ribeirão Preto, SP, Brazil) with a capacity of 3000 kg h -1 , producing 3 mm diameter extrudates, according to the methodology used by Stockhausen et al (2022).…”
Section: Experimental Dietsmentioning
confidence: 99%
See 1 more Smart Citation